Bank relationships and small-business closures during the Finnish recession of the 1990s - Helvi Kinnunen; Vesa Vihriälä (Bank of Finland, 1999)
The paper examines the role of bank relationships in business closures during the Finnish economic crisis of the early 1990s.We utilise a unique panel data set of 474 small and medium-sized firms, for which we have standard accounting information and for which we can in addition identify whether the firm had a lending relationship with the most troubled part of the banking system, namely the Savings Bank of Finland and Skopbank.By estimating a logit model we find that, even accounting for the effects of liquidity, profitability, indebtedness, age and size, firms that had a lending relationship with the savings banks concerned were more likely to close in 1992 than other firms that year or the same firms in other years.Thus being a loan customer of these banks entailed greater risk for firms than having a lending relationship with other intermediaries only in 1992, which was the year the banking sector came to a head.The result lends support to the hypothesis that financial factors affect real outcomes not only through firm and household balance sheets but also through bank behaviour.
URN:NBN:fi:bof-20140807150
Keywords: 330